2018
DOI: 10.1177/1753193418805391
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid or hyaluronic acid injections to the carpometacarpal joint of the thumb joint are associated with early complications after subsequent surgery

Abstract: Truven MarketScan® Databases were used to identify patients with thumb carpometacarpal arthritis who underwent surgical treatment. Pre-operative corticosteroid or hyaluronic acid injections were identified, as were post-operative complications. Multivariable regressions assessed the relationship between injections and complications. Of 16,268 patients, 4462 had steroid injections and 252 received hyaluronic acid injections. Twenty-one per cent (3381 patients) had post-operative complications. Diabetes and smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 28 publications
2
23
1
Order By: Relevance
“…This study adds to the literature surrounding the incidence of serious complications following intra-articular steroid injections in the hand. Our data are in stark contrast to the rate of post-surgical complications found in US data containing insured and Medicare (state-assisted health care) patients, where 21% of patients sustained any form of complication after BTOA surgery [ 12 ]. In their study, undergoing steroid injection prior to surgery increased the odds of a complication by 20%, although no absolute rate of complications was reported for those patients who had pre-operative intra-articular injections.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This study adds to the literature surrounding the incidence of serious complications following intra-articular steroid injections in the hand. Our data are in stark contrast to the rate of post-surgical complications found in US data containing insured and Medicare (state-assisted health care) patients, where 21% of patients sustained any form of complication after BTOA surgery [ 12 ]. In their study, undergoing steroid injection prior to surgery increased the odds of a complication by 20%, although no absolute rate of complications was reported for those patients who had pre-operative intra-articular injections.…”
Section: Discussioncontrasting
confidence: 80%
“…Efficacy aside, research from a recent large US insurance dataset raised concerns that BTOA steroid injections predispose patients to a higher risk of post-operative complications [ 12 ]. However, previous studies in other areas of the body have found no evidence to support this finding [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the analysis of an American database containing data of patients with TBOA, the Truven MarketScan® Databases, revealed that both steroid both HA injections were associated with early post-operative complications after surgical treatment of TBOA. In particular, infectious complications were associated with corticosteroids injections, while wound-healing complications were found to be related mainly to IA HA therapy ( Giladi et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 90-day cutoff after surgery was based on the senior author's experience in diagnosing and managing such complications, and it was a time period 1 month longer than that used in a related report. 6 The c 2 test was used for the bivariate analysis of categorical variables, and analysis of variance was used for the analysis of continuous variables. Logistic regression testing was performed to assess for relationships between the timing of injection and postoperative wound complication/infection and/or repeat surgery for wound complication/infection, after adjusting for age, sex, tobacco use, diabetes, and comorbidity burden.…”
Section: Methodsmentioning
confidence: 99%
“…1e3 There is concern about septic arthritis following an intra-articular injection due to direct bacterial inoculation of the joint from a needle and concern about the possible immunosuppressive effect of corticosteroids. 4,5 Giladi et al 6 reported a 20% increased risk of complications after CMC arthroplasty surgery, most notably infectious complications, in association with preoperative intraarticular CMC joint corticosteroid injections.…”
mentioning
confidence: 99%